Pili Protein 65.5 kDa of Klebsiella pneumoniae Induced a Decrease in IL-10 in Mice - Dini Agustina; Mei Liana Wati; Desie Dwi Wisudanti; Muhammad Ali Shodikin; Diana Chusna Mufida; Enny Suswati (Majalah Kedokteran Bandung, 2022)
Klebsiella pneumoniae is one of the leading cause of nosocomial infection worldwide with clinical isolates mostly found in Multi-Drug Resistant (MDR) or Extensively Drug-Resistant (XDR). This makes therapeutic options due to this bacteria limited. Several studies have shown that the pili protein of K. pneumoniae with different molecular weights plays a role in the virulence factor, as they are hemagglutinin and adhesin proteins. Pili protein 65.5 kDa of K. pneumoniae can be considered as the antigen candidate for vaccines. This study aimed to determine the immune response based on the IL-10 level as induced by pili protein 65.5 kDa K. pneumoniae. This study was conducted from October 2020 to March 2021 at the Faculty of Mathematics and Natural Sciences and Faculty of Medicine of Jember University. This was true experimental with post-test only controlled group design on 27 male BALB/c mice which divided into 3 groups: K1, K2, and K3. The groups were induced with sterile PBS, pili protein and Freund’s adjuvant, and Freund’s adjuvant only, respectively. Samples were drawn through cardiac puncture, then serum was taken to measure the IL-10 levels using the ELISA method. Hemagglutination test showed a positive result with 1/8 as the highest titer. Results showed that the mean IL-10 levels were 290.92±45.33; 235.05±44.53; 218.54±64,81 for K1, K2, and K3, respectively. One-way ANOVA test results showed a statistical difference between groups (p=0,019). This research shows that pili protein 65.5 kDa K. pneumoniae decreases the IL-10 level. However, when it is provided with the Freund’s Adjuvant, there is no proof of the immunogenicity when compared to the control group.